ERRORS MADE BY ENGLISH DEPARTMENT STUDENTS - HABIBI, MUCHTAR (2011)
This research is proposed to describe the errors composition made by the fourth semester of English department students of Muhammadiyah University of Surakarta. Specifically, it is to describe; 1. the type of errors, 2. the frequency of its type of errors, 3. explaining the source of error. The type of this research is descriptive qualitative research. There are thirty five student compositions analyzed. In collecting the data, the writer uses documentation method by selecting the errors which are written by fourth semester students. The steps for collecting the data are finding students' composition test with the topic given, reading and marking types of error in the student's work, writing the erroneous sentences. The collected data are analyzed by using Ellis classification of errors theory, and James source of errors theory. The results of the research show that the fourth semester of English department students of Muhammadiyah University of Surakarta still make 112 errors in their compositions. The writer finds that from the 122 data, there are eleven classifications of error based on the combination of linguistic category and surface strategy taxonomy and two classifications based on sources of error. They are TO BE (21 or 18.75%), grammar structure (21 or 18.75%), bound morpheme s/-es (15 or 13.39%), preposition (12 or 10.71 %), verb (11 or 9.83%), article (11 or 9.83%), modals (7 or 6.25%), adjective (5 or 4.46%), infinitive (4 or 3.57%), noun (3 or 2.67%), conjunction (2 or 1.78%). The highest frequency of errors that the researcher finds are TO BE errors and grammatical structure. The researcher also finds two dominant source of error, namely ; Interlingual transfer (78 or 69.64%) and intralingual transfer (34 or 30.35%).